2009
DOI: 10.1007/s00405-008-0908-1
|View full text |Cite
|
Sign up to set email alerts
|

Tympanoplasty in children

Abstract: Closure of uncomplicated tympanic membrane perforation (tympanoplasty) is usually a straightforward procedure with a good success rate. Many studies report a success rate from 60 to 99% in adults, whereas a 35-94% success rate in children. The definition of successful tympanoplasty varies from one author to other. Some authors report that an intact tympanic membrane considered a successful surgical result, whereas the other authors may also consider the postoperative hearing, as well as middle ear aeration, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 49 publications
4
57
0
1
Order By: Relevance
“…Age has previously been seen as one of the most important factors determining successful outcome for surgical management of CSOM, but a number of recent studies contradict this [27,28]. However, in settings where the surgical capacity is limited, the possibility of spontaneous healing should be considered when selecting young children for surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Age has previously been seen as one of the most important factors determining successful outcome for surgical management of CSOM, but a number of recent studies contradict this [27,28]. However, in settings where the surgical capacity is limited, the possibility of spontaneous healing should be considered when selecting young children for surgery.…”
Section: Discussionmentioning
confidence: 90%
“…COME is reduced by adenoidectomy [van den Aardweg et al, 2010], oral steroids [Simpson et al, 2011] or ventilation tube (grommet) surgery [Browning et al, 2010], although effects may be short-lived. For CSOM, antibiotics may reduce otorrhoea [Macfadyen et al, 2006], as may tympanoplasty [Sarkar et al, 2009]. Figure 6 summarises factors known or hypothesised to have an impact on susceptibility to OM.…”
Section: The Effect Of Interventionsmentioning
confidence: 99%
“…Presently, temporalis muscle fascia is the most frequently used grafting material for the repair of tympanic membrane perforation in children and recent studies have reported graft success rate of 70-91% [8,9,11,12,16,30], which is comparable to success rate of 60-99% [17,18] in adults. The problems with the use of fascia as a graft material are due to atrophy or shrinkage of graft or its nonvascularization leading to failure [19].…”
mentioning
confidence: 52%